Outbreak of Influenza and Other Respiratory Viruses in Hospitalized Patients Alongside the SARS-CoV-2 Pandemic - Fratty, Ilana S.; Reznik-Balter, Shira; Nemet, Ital; Atari, Nofar; Kliker, Limor; Sherbany, Hilda; Keller, Nathan; Stein, Michal; Mendelson, Ella; Mandelboim, Michal (Frontiers in Microbiology, 2022)
Influenza A and other respiratory viruses, circulate each winter and cause respiratory illness that can lead to severe complications in hospitalized patients. During the COVID-19 pandemic, only a few cases of respiratory viruses were detected in Israel. Our study applied RT-PCR to examine 13,674 samples collected from patients hospitalized with respiratory symptoms in 2019, 2020, and 2021 and the first half of the 2022 winter. A sharp increase in influenza A(H3N2) cases was observed in winter 2021-2022 as compared to 2020, followed by a sudden decrease in influenza cases after the detection of the SARS-CoV-2 omicron variant in Israel. Comparison of the area under the curve (AUC) of influenza infection rates during 7 consecutive winter seasons found that the minimal AUC between 2015 and 2020 was 281.1, while in 2021-2022, it was significantly lower (162.6 AUC; p=.0017), although the percentage of positive influenza cases was similar to those of previous years. The presented findings show how the dominance of influenza A(H3N2) abruptly ended upon circulation of the SARS-CoV-2 omicron variant. However, a post-COVID-19 influenza outbreak is possible, hence the planning of the next influenza vaccine is critical to ensure lower influenza-related hospitalization rates.